Field boundary features can stabilise bee populations and the pollination of mass‐flowering crops in rotational systems. Issue 10 (25th August 2021) - Gardner, Emma; Breeze, Tom D.; Clough, Yann; Smith, Henrik G.; Baldock, Katherine C. R.; Campbell, Alistair; Garratt, Michael P. D.; Gillespie, Mark A. K.; Kunin, William E.; McKerchar, Megan; Potts, Simon G.; Senapathi, Deepa; et al.
Abstract: Pollinators experience large spatiotemporal fluctuations in resource availability when mass‐flowering crops are rotated with resource‐poor cereal crops. Yet, few studies have considered the effect this has on pollinator population stability, nor how this might be mitigated to maintain consistent crop pollination services. We assess the potential of boundary features (standard narrow 1 m grassy margins, hedgerows and wide 4 m agri‐environment margins) to support and stabilise pollinator populations and pollination service in agricultural landscapes under crop rotation. Assuming a 6‐year rotation, we use a process‐based pollinator model to predict yearly pollinator population size and in‐crop visitation rates to oilseed rape and field bean across 117 study landscapes in England with varying amounts of boundary features. We model both ground‐nesting bumblebees and solitary bees and compare the predictions including and excluding boundary features from the landscapes. Ground‐nesting bumblebee populations, whose longer‐lifetime colonies benefit from continuity of resources, were larger and more stable (relative to the no‐features scenario) in landscapes with more boundary features. Ground‐nesting solitary bee populations were also larger but not significantly more stable, except with the introduction of wide permanent agri‐environment margins, due to their shorter lifetimes and shorter foraging/dispersal ranges. Crop visitation by ground‐nesting bumblebees was greater and more stable in landscapes with more boundary features, partly due to increased colony growth prior to crop flowering. Time averaged crop visitation by ground‐nesting solitary bees was slightly lower, due to females dividing their foraging time between boundary features and the crop. However, despite this, the minimum pollination service delivered was higher, due to the more stable delivery. Synthesis and applications . Field boundary features have an important role in stabilising pollinator populations and pollination service in rotational systems, although maintenance of larger semi‐natural habitat patches may be more effective for stabilising less mobile solitary bee populations. We recommend using combinations of boundary features, accounting for pollinator range when spacing features/rotating crops, and synchronising boundary feature management with crop rotation to maximise their stabilising benefits. Abstract : Field boundary features have an important role in stabilising pollinator populations and pollination service in rotational systems, although maintenance of larger semi‐natural habitat patches may be more effective for stabilising less mobile solitary bee populations. We recommend using combinations of boundary features, accounting for pollinator range when spacing features/rotating crops, and synchronising boundary feature management with crop rotation to maximise their stabilising benefits. 摘要: 当大量开花作物与资源匮乏的禾谷类作物轮作时, 传粉者会经历巨大资源可用性的时空波动。然而, 很少有研究能考虑到这种对传粉者群体数量稳定性的影响, 以及如何减轻这种情况以维持作物传粉服务的持续性。 在轮作情况下, 我们对能支持并稳定传粉者群体数量和服务的潜在农田边界特征进行了评估 (1米窄草地边缘、灌木丛和4米农业环境边界) 。假设轮作周期为6年, 我们使用基于过程的传粉模型来预测每年油菜和蚕豆的传粉者群体数量及作物访问率, 横跨了英国涵多种不同边界特征的117片研究田野。我们对地面筑巢的熊蜂和独居蜂建模, 与包括或不包括田野边界特征的预测进行对比。 在具有更多边界特征的田野中, 地面筑巢熊蜂因得益于资源连续性, 数量更多也更稳定 (相对于无特征而言) 。同样的, 地面筑巢独居蜂群体数量也更多, 但因寿命、觅食与分散范围较短, 其稳定性并没有显著提升, 除非引入广泛的永久农业环境边界。 在具有更多边界特征的田野中, 地面筑巢熊蜂的作物访问率更高也更稳定, 部分原因是作物开花前其群体生长的增加。由于雌性将它们的觅食时间分配给了作物以外的边界特征, 地面筑巢独居蜂的平均作物访问率略低, 然而由于交付更稳定, 其最低交付的授粉服务更高。 综合与应用。田间边界特征在轮作系统中, 对稳定传粉者群体数量和传粉服务具有重要作用, 尽管维护大片半自然栖息地可能会更有效的稳定移动性较差的独居蜂群体。我们建议组合使用不同的边界特征, 在间隔特征和作物轮作时考虑传粉者种群范围, 同时将边界特征管理与作物轮作同步, 以最大限度发挥它们的稳定效果。